2018
DOI: 10.3329/ajmbr.v3i4.35330
|View full text |Cite
|
Sign up to set email alerts
|

Study on clinical diseases and disorders of cattle and goat at Gopalgonj District in Bangladesh

Abstract: This clinical study was undertaken at the sadar Upazilla Livestock Office, Gopalgonj, Bangladesh to determine the general clinical prevalence of clinical diseases and disorders in cattle and goats during the study period from September to December 2016. Total animals were 105, among them cattle were 60 and goats were 45. Diagnosis was performed on the basis of general examination, physical examination and clinical examination. Clinical examinations were detected 60 (48.38% of total animals) different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 3 publications
7
6
3
Order By: Relevance
“…Tetanus: This study recorded 2.03% cases of tetanus in goats (Table 1). The result agrees with Khan et al (2018) who recorded 2.22% of cases of tetanus. Karim et al (2014) also reported 0.5% tetanus cases.…”
Section: Mastitissupporting
confidence: 92%
See 3 more Smart Citations
“…Tetanus: This study recorded 2.03% cases of tetanus in goats (Table 1). The result agrees with Khan et al (2018) who recorded 2.22% of cases of tetanus. Karim et al (2014) also reported 0.5% tetanus cases.…”
Section: Mastitissupporting
confidence: 92%
“…The present study revealed a viral disease incidence of 19.84% in goats (Table 1) and supports the findings of Khan et al (2018)…”
Section: Viral Diseases In Goatssupporting
confidence: 92%
See 2 more Smart Citations
“…As initial search results showed 344 workable scientific papers which was downed to 92 after deletion of duplicate papers. There were 39 papers selected after screening of the papers showed in the Figure 1 and among them 34 were particularly on goat (Islam et al, 2013;Karim et al, 2014;Rahman et al, 2012;Kabir et al, 2010;Rahman et al, 2011;Sardar et al, 2006;Sarker et al, 2011;Noman et al, 2011;Alam et al, 2015;Nath et al, 2014;Rabbi et al, 2014;Lucky et al, 2016;Naznin et al, 2016;Parvez, 2014;Rakshit et al, 2015;Siddiqui et al, 2016;Sarker et al, 2015;Ahmed et al, 2017;Alam et al, 2018;Amin, 2016;Bueaza, 2015;Debnath et al, 2015;Mohanto et al, 2018;Khan et al, 2018;Md. Mustafizur Rahaman, 2017;Meher et al, 2017;Sadar et al, 2018;Yousuf et al, 2017), 4 papers dealing on both sheep and goat (Hasan et al, 2012;Mondal et al, 2014;Banik et al, 2008) a single article particularly on sheep (Chowdhury, 2011).…”
Section: Search Results and Eligible Studiesmentioning
confidence: 99%